Pubertal breast development in primary school girls in Sokoto, North-western Nigeria - M O Ugege; K I Airede; A Omar; P K Ibitoye; U Chikani; A Adamu; K O Isezuo; F Jiya-Bello; J A Legbo; M Sanni (South African Medical Association, 2017)
Background. There is wide variation in normal pubertal timing among various populations. Objectives. To determine the mean age of pubertal stages of breast development and menarche, and the influence of nutrition and ethnicity on pubertal onset in primary school girls in Sokoto, North-Western Nigeria. Methods. A cross-sectional study using a multistage random sampling design was conducted on 994 primary school girls in grades 3 - 6. Weight and height measurements and Tanner breast staging were done. Body mass index (BMI) was calculated, and a BMI-for-age percentile was used to categorise nutritional status. There were four major ethnic groups. P≤0.05 was taken as showing statistical significance. Results. The participants' mean age was 10.23 years (standard deviation (SD) 1.70, range 6 - 15 years). Of the 994 girls, 628 (63.2%) were pre-pubertal, and 366 (36.8%) were pubertal. Of the latter, 158 (15.9%) were in breast stage 2, while 112 (11.3%), 70 (7.0%) and 26 (2.6%) were in breast stages 3, 4 and 5, respectively. The mean ages (SD; range) of pubertal onset and menarche were 10.50 (1.33; 8 - 13), and 12.67 (1.65; 11 - 15), years, respectively. The overnourished (overweight/obese) and Igbo ethnic group girls had early-normal pubertal onset (p=0.006 and p=0.001, respectively). Conclusion. The mean ages of Tanner breast stages 1 - 5 and menarcheal age of girls in Sokoto, North-Western Nigeria, were within the age ranges reported worldwide. Pubertal onset was influenced by nutrition.